Total Phenolic Content in Black Rice (Oryza sativa L. indica) Bran Ethanolic Extract from Two Different Regions in Java, Indonesia - Vardhani, Afifah; Anggraini, Nadia Bunga; Jufri, Mahdi; Purwaningsih, Erni; Perdanastuti, Hidayah Sunar (Tropical Biopharmaca Research Center, IPB University, 2024)
Rice bran, a rice by-product yielded by the milling process, has recently been recognized as a potential source of natural active constituents. Black rice bran has the highest antioxidant capacity compared to white and brown rice bran. It is correlated with the contribution of phenolic compounds in rice bran. The purpose of this study was to determine the total phenolic content in black rice (Oryza sativa L. indica) bran ethanolic extract from two different regions in Java, Indonesia, using Folin-Ciocalteu Reagent (FCR). Black rice bran samples used in this study were planted in Ciletuh Geopark Sukabumi, West Java (BRBE1), and Karanganyar Regency, Central Java (BRBE2). The parameters observed were total phenolic content, and the result was statistically tested with an unpaired t-test by GraphPad Prism 8.3.0 application. The samples contained 175.48 mg GAE/g extract in BRBE1 and 174.39 mg GAE/g extract in BRBE2. There was no significant difference based on these results. It can be concluded that both samples contained phenolic compounds and statistically, there was no significant difference.